Relationship Between Knowledge and Self-Management in Diabetes Mellitus Patients - Soamole, Idham; Rumaolat, Windarti; Tunny, Hasna (UNIMUS Web Conferences, 2026)
Background: Diabetes Mellitus (DM) is a non-communicable disease. Uncontrolled diabetes mellitus can cause complications. One important factor in preventing complications is through self- management by the patient, but there is still a gap between the ideal expectations of patient self-management and the reality in the field. This indicates that there are still important factors that have not been optimally addressed, namely patient knowledge about self-management. Objective: To analyze the relationship between knowledge and self- management in diabetes mellitus patients. Method: This study used a quantitative approach with a cross-sectional design. A sample of 84 respondents was selected using a purposive sampling technique in the working area of the CH M Tiahahu Health Center, Ambon City. The instrument used was a questionnaire that had been tested for validity and reliability. Data analysis was carried out using the Mann-Whitney test. Results: The majority of respondents were elderly (53.5%), female (56%), and highly educated (51.2%). Most respondents were unemployed (27.4%), and 45.2% had new diabetes. The results of the study Statistical tests showed a p value = 0.000 (p <0.05). Discussion: Knowledge is the result of knowing and occurs after a person senses an object, including through education, information, or experience. Therefore, the better a person's knowledge, the more likely their health behavior will also be better. Self-management is a key factor in the long-term management of Diabetes Mellitus, as this disease is chronic and requires active involvement from the patient in daily life. Conclusion: There is a significant relationship between the level of knowledge and self-management abilities in diabetes mellitus patients in the working area of the Ch. M. Tiahahu Health Center, Ambon City, based on the test results.